Ethical dimensions of health policy - Danis, Marion (Oxford University Press, 2002)
This book takes the conversation between bioethics and health policy to a new level. Moving beyond principles and normative frameworks, bioethicists writing in the volume consider the actual policy problems faced by health care systems, while policy-makers reflect on the moral values inherent in both the process and content of health policy. The result is a vigorous dialogue with some of the nation\'s leading experts at the interface of ethics and health policy. the book provides a history of the values implicit in U.S. health policy, a discussion of the federal and state roles in policy making, an ethical examination of the social goals expressed through various policies, an analysis of the role of public opinion in the creation of health policy, and an exploration of the value of the private sector in health policy. In addition, the authors examine some of the major ethical controversies in health policy, such as the challenge of balancing ethical concerns with economic realities, the need to allocate scarce health resources, the call for heightened accountability, and the impact of various policies on vulnerable populations. The book concludes with an examination of the ethical issues in health services research, including the threats to privacy that arise in such research. To a greater extent than any previous volume, it establishes a strong connection between the disciplines of medical ethics and health policy.
Keywords: Health Policy; veřejné zdravotnictví; zdravotní politika; management, organizace a řízení zdravotnictví